2010
DOI: 10.15365/cate.3192010
|View full text |Cite
|
Sign up to set email alerts
|

Examining Motivations and Recruitment Strategies for Urban Forestry Volunteers

Abstract: Few studies in urban forestry have examined the motivations of urban forestry volunteers. In this research, two social psychological theories (Volunteer Functions Inventory and Volunteer Process Model) are utilized to examine motivations for participating in tree planting activities. The Volunteer Functions Inventory can be used to examine the needs, goals and motivations that individuals seek to fulfill through volunteerism. The Volunteer Process Model sheds light on the antecedents, experiences and consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 66 publications
1
36
0
Order By: Relevance
“…Urban forestry volunteers have reported that trees planted in parks and in residential neighborhoods produce the same benefits (e.g. esthetic benefits, general environmental improvement, shade, clean air, habitat for wildlife), but to a different degree in each setting, with environmental and community benefits being more associated with park trees than with street trees in residential areas (Moskell, Broussard Allred, & Ferenz, 2010). These beliefs may be dependent upon people's experiences with trees in different settings.…”
Section: Planting Location Of Treesmentioning
confidence: 99%
“…Urban forestry volunteers have reported that trees planted in parks and in residential neighborhoods produce the same benefits (e.g. esthetic benefits, general environmental improvement, shade, clean air, habitat for wildlife), but to a different degree in each setting, with environmental and community benefits being more associated with park trees than with street trees in residential areas (Moskell, Broussard Allred, & Ferenz, 2010). These beliefs may be dependent upon people's experiences with trees in different settings.…”
Section: Planting Location Of Treesmentioning
confidence: 99%
“…Others conducted field ecology research on forest restoration initiativesSimmons 2010;Falxa-Raymond 2011). Still others examined community engagement, stewardship, volunteerism, and green jobs(Fisher et al 2011;Moskell et al 2010;Falxa-Raymond et al 2013…”
mentioning
confidence: 99%
“…The plants come at no monetary cost to those who volunteer, nevertheless, dues come in the form of expectations, not only to do the planting, but to put in the necessary time and effort through weeding and watering to promote plant survival. The WCC asks environmental community groups to agree to look after plants for at least five years, and such requests are at least in part due to increasing local government budgetary restraints (Moskell, Allred, and Ferenz 2010). However, restraint is not the full story as we might conceive that councils' motivations are as complex as volunteers' and that they are influenced by the work of urban geographers, urban planners, and urban ecologists who suggest that building partnerships between government, developers, and citizens is the most effective way to advance and augment urban greening practices (Jim 2004).…”
Section: Study Contextmentioning
confidence: 99%